2021
DOI: 10.1002/lary.29848
|View full text |Cite
|
Sign up to set email alerts
|

Application and Efficiency of Transnasal Humidified Rapid‐Insufflation Ventilatory Exchange in Laryngeal Microsurgery

Abstract: Objectives/Hypothesis This study aimed to analyze the feasibility of transnasal humidified rapid‐insufflation ventilatory exchange (THRIVE) during laryngeal microsurgery (LMS) and investigated its efficiency and application according to the location of the lesion. Study Design Retrospective chart review. Methods Patients over 20 years of age who underwent LMS without underlying cardiac, pulmonary, or cerebrovascular disease were retrospectively reviewed. Overall, 54 patients with endotracheal intubation (ETI) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(21 citation statements)
references
References 30 publications
0
14
0
Order By: Relevance
“…Three studies [ 33 - 35 ] including 236 patients reported the duration of surgery as an outcome. The duration of surgery was significantly decreased in the THRIVE group as show in Figure 2 (OR -4.92, 95%CI -7.73 to -2.11) (GRADE: Moderate).…”
Section: Reviewmentioning
confidence: 99%
See 3 more Smart Citations
“…Three studies [ 33 - 35 ] including 236 patients reported the duration of surgery as an outcome. The duration of surgery was significantly decreased in the THRIVE group as show in Figure 2 (OR -4.92, 95%CI -7.73 to -2.11) (GRADE: Moderate).…”
Section: Reviewmentioning
confidence: 99%
“…Laser is occasionally used in laryngeal surgery and airway fire is a potentially fatal complication. Several of the studies in both the HFNC and jet ventilation groups included patients undergoing laser surgery [ 15 , 46 , 35 ], with no cases of airway fire reported. Some studies have reported the use of THRIVE during laser cases without adverse events or airway fire by turning off the oxygen flow for 40 seconds before the use of laser or by decreasing the fraction of inspired oxygen and suctioning airway gases [ 5 , 46 ].…”
Section: Reviewmentioning
confidence: 99%
See 2 more Smart Citations
“…Transnasal humidified rapid-insufflation ventilatory exchange (THRIVE) is a new technique of apneic oxygenation [ 2 , 3 ]. Several exploratory studies have suggested that THRIVE could be used for apneic oxygenation during anesthesia induction and difficult airway management [ 3 10 ]. However, due to the insufficient carbon dioxide exchange capacity, the safety of applying THRIVE to patients without spontaneous respiration needs further evaluation.…”
Section: Introductionmentioning
confidence: 99%